Exploring Civic Engagement through Student-Led Initiatives - Anthony Angwaomaodoko, Ejuchegahi (International Research in Education, 2024)
Civic engagement involves a collective action to address issues of the public, by promoting the quality of life through both political and non-political process. In a time where there are growing concerns over civic participation and cohesion, understanding the relationship between student-led initiatives and promoting civic engagement is very important. The study focuses on exploring civic engagement through student-led initiatives. A thorough review of literature was carried out in this study which encompass the overview of student led initiatives and civic engagement, benefits, factors influencing and challenges associated with student led initiatives with special focus on addressing societal issues. The study highlights the importance of these initiatives to students as it helps them to develop important skills which they would find useful in solving several problems in the community and society at large. The study also offers insight to educators, key community members to promote student led initiatives as it fosters a meaningful and productive civic engagement and societal change at all levels.